Novas perspectivas no ensino de desenho técnico - Lima, Rafaela de Araujo Sampaio (Brasil, 2020)
during the Professional Master’s Degree in Technological Teaching promoted by the Federal Institute of Education, Science and Technology of Amazonas (IFAM) and its purpose is to consolidate and disseminate the didactic modality of the field class adapted to the discipline of Technical Drawing. In this material we provide guidelines for the teacher who wishes to draw a new perspective on the teaching of Technical Drawing, overcoming the barriers of the classroom and using different spaces in the teaching/ learning process. For this, we characterize formal spaces, non-formal spaces and formal non-conventional spaces of teaching; we portrayed the previous and later moments and their association to the field class; we present criteria that can be adopted in the decision making on the site of the field lesson and contents that can be included in the field activity script and we describe the steps of a field class in the discipline of Technical Drawing. In this way, we hope to contribute to the teachers of the discipline use other spaces in the process of knowledge construction, aiming to provide students with a reality close to their future field of application, the application of theoretical knowledge acquired and the development skills needed for professional practice.